Sustained Release Spherical Agglomerates of Tiaprofenic Acid Prepared by Quasi-emulsion Solvent Diffusion Method - Sorathia, Kishorkumar R. (Asian Journal of Pharmaceutics (AJP), 2016)
Purpose: The purpose of this study was to prepare sustained release (SR) spherical agglomerates with improved flow and compression properties using spherical crystallization technique. Methods: The spherical agglomerates of tiaprofenic acid were prepared by using quasi-emulsion solvent diffusion technique. Acetone and 0.1 N HCl were used as good solvent and poor solvent, respectively, while Eudragit RS100 and RL100 were used as release retardant polymers. The prepared agglomerates were evaluated for micromeritic, mechanical, and compression properties. Morphology and release characteristic of agglomerates was evaluated by scanning electron microscopy (SEM) analysis and in-vitro dissolution study, respectively. Differential scanning calorimetry (DSC) and Fourier transform-infrared (FT-IR) were performed to determine the presence of any drug-polymer interaction. Results: Spherical agglomerates were generated with uniform dispersion of drug within the matrix of polymer having size in the range of 100-500 Î¼m. Due to spherical shape, agglomerates showed excellent flow, packability, compatibility, and mechanical properties. Good mechanical strength was indicated through higher crushing strength of agglomerates. Improved compressibility of agglomerates was indicated by lower Ïƒ0 value in Heckel plot analysis, higher tensile strength, and lower elastic recovery compared to pure drug crystals. Sphericity and surface smoothness of agglomerates were revealed in SEM photos. In-vitro dissolution study indicated SR of drug for prolonged period. DSC and FT-IR indicated the absence of drug-polymer interaction and no change in molecular structure of drug due to agglomeration in the presence of polymers. Conclusion: Quasi-emulsion solvent diffusion technique has been successfully utilized for the development of directly compressible SR spherical agglomerates of poorly soluble drugs like tiaprofenic acid.